Socio-Demographic Factors Affecting Attitude towards Office Gastrodiplomacy among Local Government Employees - Bajar, Jayson Troy F.; Dela Peña, Renia F. (Silliman Journal, 2022)
The meaning of food is redefined. Human development witnessed the politicization of food and how key messages were relayed through the food we share or what we simply call ”gastrodiplomacy.” This study was conducted to determine the socio-demographic factors that affect attitude towards office gastrodiplomacy among employees of a local government unit in the Philippines. This is a descriptive-relational study that employed a one-shot survey among 327 respondents. Data were collected using a two-part questionnaire that included questions on: a) socio-demographic characteristics consisting of age, sex, educational attainment, length of service, monthly income, and nature of job position; and the b) researcher-made instrument on attitude towards office gastrodiplomacy. It was found out that respondents had a generally ‘high positive attitude’ towards office gastrodiplomacy, although only age and length of service were significantly related. The findings of this study provide a breakthrough on research on office gastrodiplomacy in the Philippines, where such practice is prevalent yet understudied or has not been tackled at all as of writing.